2020
DOI: 10.1101/2020.07.31.20165225
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved Sensitivity of Digits-in-Noise Test to High-Frequency Hearing Loss

Abstract: ObjectivesHearing loss is most commonly observed at high frequencies. High-frequency hearing loss (HFHL) precedes and predicts hearing loss at lower frequencies. It was previously shown that an automated, self-administered digits-in-noise (DIN) test can be sensitized for detection of HFHL by low-pass filtering the speech-shaped masking noise at 1.5 kHz. This study was designed to investigate whether sensitivity of the DIN to HFHL can be enhanced further using low-pass noise filters with higher cutoff frequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The lab-DIN test was administered using Sennheiser 215 headphones connected to an iPad in a double-walled sound booth meeting criteria of ANSI S3.1. No test-retest was done for the lab testing since the reliability of lab procedures has already been established (Motlagh-Zadeh et al, 2020).…”
Section: Lab Implementationmentioning
confidence: 99%
See 3 more Smart Citations
“…The lab-DIN test was administered using Sennheiser 215 headphones connected to an iPad in a double-walled sound booth meeting criteria of ANSI S3.1. No test-retest was done for the lab testing since the reliability of lab procedures has already been established (Motlagh-Zadeh et al, 2020).…”
Section: Lab Implementationmentioning
confidence: 99%
“…A speech reception threshold (SRT) is the usual outcome measure, the speech (digit) signal-tonoise ratio at which three successive digits are all correctly recognized on 50% of presentations (Vlaming et al 2014). During the past 10 years, the efficacy and sensitivity of the standard DIN test have been substantially increased using various test modifications such as low-pass filtering of the noise (Vlaming et al 2014;Motlagh Zadeh et al 2019;Motlagh Zadeh et al 2020) and antiphasic presentation of the digits (De Sousa et al 2018;De Sousa et al 2020). For example, De Sousa et al (2018) showed that presenting digits that are phase inverted (antiphasic) between the ears, while leaving the masking noise interaurally in-phase, significantly improves sensitivity of DIN test to asymmetric or unilateral sensorineural hearing loss (area under the receiver operating characteristic curve, AUROC = 0.94).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations